Immunonutrition as an adjuvant therapy for burns - Tan, Hannah B.; Danilla, Stefan; Murray, Alexandra; Serra, Ramón; El Dib, Regina [UNESP]; Henderson, Tom O.W.; Wasiak, Jason (Wiley, 2014)
Background: With burn injuries involving a large total body surface area (TBSA), the body can enter a state of breakdown, resulting in a condition similar to that seen with severe lack of proper nutrition. In addition, destruction of the effective skin barrier leads to loss of normal body temperature regulation and increased risk of infection and fluid loss. Nutritional support is common in the management of severe burn injury, and the approach of altering immune system activity with specific nutrients is termed immunonutrition. Three potential targets have been identified for immunonutrition: mucosal barrier function, cellular defence and local or systemic inflammation. The nutrients most often used for immunonutrition are glutamine, arginine, branched-chain amino acids (BCAAs), omega-3 (n-3) fatty acids and nucleotides. Objectives: To assess the effects of a diet with added immunonutrients (glutamine, arginine, BCAAs, n-3 fatty acids (fish oil), combined immunonutrients or precursors to known immunonutrients) versus an isonitrogenous diet (a diet wherein the overall protein content is held constant, but individual constituents may be changed) on clinical outcomes in patients with severe burn injury. Search methods: The search was run on 12 August 2012. We searched the Cochrane Injuries Group's Specialised Register, The Cochrane Library, MEDLINE (OvidSP), Embase (OvidSP), ISI WOS SCI-EXPANDED & CPCI-S and four other databases. We handsearched relevant journals and conference proceedings, screened reference lists and contacted pharmaceutical companies. We updated this search in October 2014, but the results of this updated search have not yet been incorporated. Selection criteria: Randomised controlled trials comparing the addition of immunonutrients to a standard nutritional regimen versus an isonitrogenated diet or another immunonutrient agent. Data collection and analysis: Two review authors were responsible for handsearching, reviewing electronic search results and identifying potentially eligible studies. Three review authors retrieved and reviewed independently full reports of these studies for inclusion. They resolved differences by discussion. Two review authors independently extracted and entered data from the included studies. A third review author checked these data. Two review authors independently assessed the risk of bias of each included study and resolved disagreements through discussion or consultation with the third and fourth review authors. Outcome measures of interest were mortality, hospital length of stay, rate of burn wound infection and rate of non-wound infection (bacteraemia, pneumonia and urinary tract infection). Main results: We identified 16 trials involving 678 people that met the inclusion criteria. A total of 16 trials contributed data to the analysis. Of note, most studies failed to report on randomisation methods and intention-to-treat principles; therefore study results should be interpreted with caution. Glutamine was the most common immunonutrient and was given in seven of the 16 included studies. Use of glutamine compared with an isonitrogenous control led to a reduction in length of hospital stay (mean stay -5.65 days, 95% confidence interval (CI) -8.09 to -3.22) and reduced mortality (pooled risk ratio (RR) 0.25, 95% CI 0.08 to 0.78). However, because of the small sample size, it is likely that these results reflect a false-positive effect. No study findings suggest that glutamine has an effect on burn wound infection or on non-wound infection. All other agents investigated showed no evidence of an effect on mortality, length of stay or burn wound infection or non-wound infection rates. Authors' conclusions: Although we found evidence of an effect of glutamine on mortality reduction, this finding should be taken with care. The number of study participants analysed in this systematic review was not sufficient to permit conclusions that recommend or refute the use of glutamine. Glutamine may be effective in reducing mortality, but larger studies are needed to determine the overall effects of glutamine and other immunonutrition agents.